BALANCE SCORECARD : ANALISIS KEPEMIMPINAN, MOTIVASI DAN KEPUASAN KERJA PERAWAT DENGAN KINERJA RUMAH SAKIT - Janes Jainurakhma (Jurnal Ilmiah Kesehatan Media Husada, 2022)
Abstract The spirit of work in employees arised when the love of work is high, and it was formed because of motivation and job satisfaction in the employee, in addition to the existence of a leadership style that’s able to provide comfort to employees in work. The study's goal was to analyze nurses' leadership relationships, motivation and job satisfaction with hospital performance using the balance scorecard approach at Gatoel Mojokerto Hospital. The design of this research is crossectional analytics. These variables are leadership, motivation, and job satisfaction as independent variables and hospital performance as dependent variable. The population of this study are all nurses in Gatoel Hospital Mojokerto City as many as 138 nurses. The sample was taken with a simple random sampling technique as many as 102 respondents. The data was collected with a questionnaire instrument and tested with the rho spearman test. The results showed the p value al of independent variables showed a value = 0.00 so that the value of p value < 0.05 then this shows that there is a relationship between independent variables (leadership, motivation, and job satisfaction of nurses) with variable dependent (performance). To maximize the achievement of the implementation of balanced scorecard as part of the management control system, hospital management should not only take measurements but also look at supporting factors and obstacles in each indicator so that further efforts can be made to the existence of the main performance indicators.